Medieval wisdom for modern Christians : finding authentic faith in a forgotten age with C.S. Lewis - Armstrong, Chris R. (Christopher Robert), 1963- (Grand Rapids, MI : Brazos Press, a division of Baker Publishing Group, 2016)
Many Christians today tend to view the story of medieval faith as a cautionary tale. Too often, they dismiss the Middle Ages as a period of corruption and decay in the church. They seem to assume that the church apostatized from true Christianity after it gained cultural influence in the time of Constantine, and the faith was only later recovered by the sixteenth-century Reformers or even the eighteenth-century revivalists. As a result, the riches and wisdom of the medieval period have remained largely inaccessible to modern Protestants. Church historian Chris Armstrong helps readers see beyond modern caricatures of the medieval church to the animating Christian spirit of that age. He believes today's church could learn a number of lessons from medieval faith, such as how the gospel speaks to ordinary, embodied human life in this world. Medieval Wisdom for Modern Christians explores key ideas, figures, and movements from the Middle Ages in conversation with C. S. Lewis and other thinkers, helping contemporary Christians discover authentic faith and renewal in a forgotten age.
My angle of approach -- C.S. Lewis-a modern medieval man -- Getting rooted: tradition as source of truth -- Getting thoughtful: the medieval passion for theological knowledge -- Getting moral: the ethical fabric of medieval faith -- Getting merciful: why medievals invented the hospital -- Getting earthy: God's second book-the natural world -- Getting passionate: medieval faith as a religion of the heart -- Getting human: how the incarnation lifts up our humanness -- Getting it together: responding to our medieval heritage and reflecting on the ascetic and monastic paths.
Includes index.
Includes bibliographical references and index.
Keywords: Church history -- Middle Ages, 600-1500.; Christian literature